Surface and Interface Properties in Thin‐Film Solar Cells: Using Soft X‐rays and Electrons to Unravel the Electronic and Chemical Structure. Issue 26 (21st February 2019) - Weinhardt, Lothar; Hauschild, Dirk; Heske, Clemens
Abstract: Thin‐film solar cells have great potential to overtake the currently dominant silicon‐based solar cell technologies in a strongly growing market. Such thin‐film devices consist of a multilayer structure, for which charge‐carrier transport across interfaces plays a crucial role in minimizing the associated recombination losses and achieving high solar conversion efficiencies. Further development can strongly profit from a high‐level characterization that gives a local, electronic, and chemical picture of the interface properties, which allows for an insight‐driven optimization. Herein, the authors' recent progress of applying a "toolbox" of high‐level laboratory‐ and synchrotron‐based electron and soft X‐ray spectroscopies to characterize the chemical and electronic properties of such applied interfaces is provided. With this toolbox in hand, the activities are paired with those of experts in thin‐film solar cell preparation at the cutting edge of current developments to obtain a deeper understanding of the recent improvements in the field, e.g., by studying the influence of so‐called "post‐deposition treatments", as well as characterizing the properties of interfaces with alternative buffer layer materials that give superior efficiencies on large, module‐sized areas. Abstract : Electron and soft X‐ray spectroscopies are powerful techniques to study the chemical and electronic structure of surfaces and interfaces. The use of these techniques to study solar devices and to unravel some of the most pertinent aspects of recent cutting‐edge developments (and world‐record efficiency improvements) in chalcopyrite thin‐film solar cells is discussed.